Utility of magnetic resonance spectroscopic imaging for human epilepsy - Pan, Jullie W.; Kuzniecky, Ruben I. (Quantitative Imaging in Medicine and Surgery; Vol 5, No 2 (April 01, 2015): Quantitative Imaging in Medicine and Surgery (Epilepsy), 2015)
This review discusses the potential utility of broad based use of magnetic resonance (MR) spectroscopic imaging for human epilepsy and seizure localization. The clinical challenges are well known to the epilepsy community, intrinsic in the variability of location, volumetric size and network extent of epileptogenic tissue in individual patients. The technical challenges are also evident, with high performance requirements in multiple steps, including magnet homogeneity, detector performance, sequence design, speed of acquisition in addition to large territory spectral processing. We consider how MR spectroscopy and spectroscopic imaging has been informative for epilepsy thus far, with specific attention to what is measured, the interpretation of such measurements and technical performance challenges. Examples are shown from medial temporal lobe and neocortical epilepsies are considered from 4T, 7T and most recently 3T.